Effect of Altitude on Age of Loss of Ambulation in Boys with Duchene Muscular Dystrophy - Pokharel, Rohit; Agrawal, Jagdish Prasad; Chaudhary, Bidhyananda; Poudyal, Amod Kumar; Takeda, Atsuto; Ishikawa, Yuka; Nambu, Yoshinori; Takeuchi, Atsuko; Nishio, Hisahide; Matsuo, Masafumi (Journal of Institute of Medicine Nepal, 2025)
Introduction Early loss-of-ambulation (LOA) and death at young age are inevitable in Duchene muscular dystrophy (DMD). Definite treatment of DMD is not available till date. Prolongation of ambulation and management of complications is the goal of treatment. In sports, high-altitude training is popular to improve athletic performance. We investigated the influence of altitude on DMD in relation to age at LOA. Methods It was a cross-sectional study done on 91 DMD patients, who have lost their ambulation, using the database of Muscular Dystrophy Foundation-Nepal. DMD boys living in different elevations of Nepal were divided into <200m (plain), 200-700m (intermediate), 700-1000m (middle), and >1000m (high) groups, and the age at LOA was recorded. Findings were tabulated and analyzed statistically using student's t-test and Log Rank test, with p <0.05 considered significant. Results Out of 91 DMD cases registered, 36 (39.6%), 34 (37.4%) were from plain (Terai) area and high land area of Nepal respectively; accounting 77% of the total patients. The median age at LOA for each group increased with elevation, and the LOA age in the high-land group (median ± SD; 11.20 ± 2.78) was significantly higher than that in the low-land group (9.62 ± 2.02) by about 2 years (p <0.005). Conclusion Our study indicated a longer period of independent walking for DMD patients living in high altitude areas. DMD boys might benefit by rehabilitation at higher altitude.